GENDER STEREOTYPES AND PROFESSIONS SUITABLE FOR WOMEN - Khakimov, Orziqul; Donaboyeva, Dilnoza (Science technology&Digital finance, 2023)
Gender stereotypes have also influenced the choice of occupation by women and men. For example, a firefighter means that a man is embodied in front of us, while the profession of a nurse is considered only that of a woman. In fact, this is nothing more than stereotypical thinking. In the minds of many, women and men are divided by what professions are suitable or not.